2000
DOI: 10.1097/00004770-200010000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Enterococcus faecalis in Previously Root-Filled Canals in a Lithuanian Population

Abstract: The occurrence of Enterococcus faecalis in root canals of previously root filled teeth with apical periodontitis requiring retreatment was studied in Lithuanian patients. Twenty-five asymptomatic teeth were included in the study. Avoiding contamination microbiological samples were taken from the canals before and after preparation and irrigation with sodium hypochlorite and EDTA. Microbes were isolated from 20 of 25 teeth. E. faecalis was isolated from 14 of those 20 culture positive teeth, usually in pure cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
219
1
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(258 citation statements)
references
References 12 publications
11
219
1
19
Order By: Relevance
“…In terms of oral disease, E. faecalis is the most commonly isolated species from infected root canals of teeth that fail to heal following root canal therapy (Sundqvist et al, 1998;Peciuliene et al, 2000;Pinheiro et al, 2003 Complicating management of these infections is the development of resistance among many enterococcal strains against many of the available, previously effective antibiotics, including vancomycin (Havard et al, 1959;Murray & Mederski-Samaroj, 1983;Uttley et al, 1988;Grayson et al, 1991;Bonten et al, 2001;Tenover & McDonald, 2005). Although a modest number of new antibiotics, such as linezolid and daptomycin, have been developed to provide treatment alternatives in cases of infection by organisms that are resistant to all previously available antibiotics, there have been numerous reports of resistance by E. faecalis and E. faecium strains to these antibiotics as well (Eliopoulos et al, 1998;Prystowsky et al, 2001;Gonzales et al, 2001;Herrero et al, 2002;Johnson et al, 2004;Munoz-Price et al, 2005;Kanafani et al, 2007;Hidron et al, 2008;Marshall et al, 2009;Kelesidis et al, 2011;Ross et al, 2011;Ntokou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of oral disease, E. faecalis is the most commonly isolated species from infected root canals of teeth that fail to heal following root canal therapy (Sundqvist et al, 1998;Peciuliene et al, 2000;Pinheiro et al, 2003 Complicating management of these infections is the development of resistance among many enterococcal strains against many of the available, previously effective antibiotics, including vancomycin (Havard et al, 1959;Murray & Mederski-Samaroj, 1983;Uttley et al, 1988;Grayson et al, 1991;Bonten et al, 2001;Tenover & McDonald, 2005). Although a modest number of new antibiotics, such as linezolid and daptomycin, have been developed to provide treatment alternatives in cases of infection by organisms that are resistant to all previously available antibiotics, there have been numerous reports of resistance by E. faecalis and E. faecium strains to these antibiotics as well (Eliopoulos et al, 1998;Prystowsky et al, 2001;Gonzales et al, 2001;Herrero et al, 2002;Johnson et al, 2004;Munoz-Price et al, 2005;Kanafani et al, 2007;Hidron et al, 2008;Marshall et al, 2009;Kelesidis et al, 2011;Ross et al, 2011;Ntokou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a Lithuanian population study, 56% of the cases were reported to be positive for E. faecalis, using only culture techniques for identification 21 . In this study, 45% of the samples were positive for Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…17,51,52 Enterococci, which are seldom found in these circumstances, have been isolated from teeth undergoing endodontic treatment and previously root treated teeth. [53][54][55][56] In a study of root filled teeth with apical periodontitis 69% of the bacterial strains recovered from the root canals were faculative anaerobes. 53,54 Enterococci were isolated in 50% of the infective cases and were the most frequently isolated.…”
Section: Endodonticsmentioning
confidence: 99%